It’s second nature: designing nature play spaces to inspire creativity in early childhood - Ramirez, Adyline (My University, 2025)
Creativity is a vital life skill declining among Americans, disproportionately affecting young children. Creativity is crucial because it empowers individuals and catalyzes societal progress. While creativity is often associated with the arts (painting, drawing, song, dance, performance), it is also evident in critical thinking processes and problem-solving skills. Everybody possesses creative potential; it is not a born trait but rather a skill one can develop. Many argue that creativity should be prioritized in formal education, particularly in preschool or before. In early childhood, a child’s play and imagination are considered a manifestation of their creativity because it is the primary way they interact with and explore the world. Playgrounds provide settings in the built environment to play, creating social interaction and physical activity hubs. Nature-based play offers children significant creative development opportunities due to their restorative qualities, living essence, and unique play opportunities. With preschool enrollment at a record high, planners and designers have a growing responsibility to recognize the benefits of nature play and its power to inspire creativity in early childhood settings. This research explored widely accepted design practices and precedent examples of nature play spaces, investigating landscape strategies to inspire creative thinking in young children. Background conditions were gathered through the literature review, informing a design guidelines review and precedent studies. Findings from the design guidelines review and precedent studies were translated to inform a conceptual re-design of a nature playspace at the Center for Child Development (CCD) at Kansas State University, implementing design techniques to boost creativity in children aged six weeks to five years old. The projective design outcome of the CCD inspires creativity in early childhood by balancing structured play possibilities and open-ended exploration supported by the environment.
Keywords: Nature play; Creativity; Early childhood; Playground design; Loose parts; Dramatic play